2016
DOI: 10.1038/srep19503
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sulfur dioxide alleviates collagen remodeling via inhibiting TGF-β/Smad pathway in vascular smooth muscle cells

Abstract: The study was designed to investigate the role of endogenous sulfur dioxide (SO2) in collagen remodeling and its mechanisms in vascular smooth muscle cells (VSMCs). Overexpression of endogenous SO2 synthase aspartate aminotransferase (AAT) 1 or 2 increased SO2 levels and inhibited collagen I and III expressions induced by transforming growth factor (TGF)-β1 in VSMCs. In contrast, AAT1 or AAT2 knockdown induced a severe collagen deposition in TGF-β1-treated VSMCs. Furthermore, AAT1 or AAT2 overexpression suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…To investigate the effects of ET-1 on the endogenous SO 2 pathway and its mechanisms in VSMCs, cells were divided into the following groups: control group, 10 -6 M ET-1 group, N-acetyl-L-cysteine (NAC) group, NAC+10 -6 M ET-1 group, glutathione (GSH) group, and GSH+10 -6 M ET-1 group. [27]. After drug stimulation for 48 h, an SO 2 fluorescent probe working fluid (10 μM) was added to the medium of cells and incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the effects of ET-1 on the endogenous SO 2 pathway and its mechanisms in VSMCs, cells were divided into the following groups: control group, 10 -6 M ET-1 group, N-acetyl-L-cysteine (NAC) group, NAC+10 -6 M ET-1 group, glutathione (GSH) group, and GSH+10 -6 M ET-1 group. [27]. After drug stimulation for 48 h, an SO 2 fluorescent probe working fluid (10 μM) was added to the medium of cells and incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that SO 2 improved the ISO-induced myocardial apoptosis of the rats ( 32 ). Some studies have shown that SO 2 gas performs many biological functions, such as vasodilation, improvement of vascular and collagen remodelling; it also inhibits inflammation and autoxidation and exerts an important protective effect on vascular diseases ( 33 36 ), such as pulmonary arterial hypertension, myocardial ischaemia-reperfusion injury, myocardial hypertrophy, spontaneous hypertension and acute lung injury ( 37 40 ). However, the role of SO 2 in diabetic myocardial fibrosis and the relevant regulatory mechanism have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Skin care is crucial in preventing skin breakdown and venous ulcers especially during kidney dysfunction [ 15 ]. Sometimes permanent deformation also sets in skin when the remodelling capability of collagen [ 16 ] is collapsed, as collagen is the one that binds muscles and bones with skin. The exterior manifestation of muscular changes, hydration [ 17 ] and wrinkles contribute to skin texture when viewed through a digital camera.…”
Section: Gfr Computationmentioning
confidence: 99%